2016
DOI: 10.2460/ajvr.77.8.898
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of humoral insulin-like growth factor-1, platelet-derived growth factor-BB, transforming growth factor-β1, and interleukin-1 receptor antagonist concentrations among equine autologous blood-derived preparations

Abstract: OBJECTIVE To compare humoral insulin-like growth factor (IGF)-1, platelet-derived growth factor (PDGF)-BB, transforming growth factor (TGF)-β1, and interleukin-1 receptor antagonist (IL-1Ra) concentrations in plasma and 3 types of equine autologous blood-derived preparations (ABPs). SAMPLE Blood and ABP samples from 12 horses. PROCEDURES Blood samples from each horse were processed by use of commercial systems to obtain plasma, platelet concentrate, conditioned serum, and aqueous platelet lysate. Half of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
11
0
3
Order By: Relevance
“…When activated, platelets release multiple growth factors and cytokines from their α granules ( 29 , 34 ) including TGF-β 1 and PDGF-ββ, which have been repeatedly evaluated in many other related studies ( 23 25 , 35 , 36 ). The authors chose to evaluate concentrations of TGF-β 1 and PDGF-ββ because these growth factors are found in the high concentrations in equine platelets ( 24 ) giving us the opportunity to more accurately quantify concentration changes relative to our treatment groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When activated, platelets release multiple growth factors and cytokines from their α granules ( 29 , 34 ) including TGF-β 1 and PDGF-ββ, which have been repeatedly evaluated in many other related studies ( 23 25 , 35 , 36 ). The authors chose to evaluate concentrations of TGF-β 1 and PDGF-ββ because these growth factors are found in the high concentrations in equine platelets ( 24 ) giving us the opportunity to more accurately quantify concentration changes relative to our treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, as mentioned earlier, freezing and thawing the PRP sample would preclude its use as a stall-side therapy. It has also been suggested that a freeze/thaw cycle results in platelet lysing and complete degranulation ( 36 , 39 ) rather than platelet activation. It has been shown that platelets may continue to release growth factors for several days after reaching the injury site, because the half-life of platelets has been estimated to be 5–7 days ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sowohl im Blut als auch im Knochenmark befinden sich viele verschiedene anabol und anti-katabol wirkende Zytokine, wie Wachstumsfaktoren (WF) und andere Peptide, die eine solche Wirkung ausüben können (Smith et al 2006, Hraha et al 2011, Boswell et al 2012, Textor 2014. Ursprünglich befindet sich der größte Anteil dieser Botenstoffe intrazellulär, hauptsächlich in Thrombozyten und Leukozyten, aber ein gewisser Teil liegt extrazellulär in bioaktiver humoraler Form im Plasma von Blut und Knochenmark vor (Korf-Klingebiel et al 2008, McCarrel und Fortier 2009, Soltan et al 2009, Boswell et al 2012, Ionita et al 2016. Werden Thrombozyten und Leukozyten aktiviert, reagieren sie darauf mit der Freisetzung dieser Moleküle wodurch diese ihre Wirksamkeit entfalten können (Boswell et al 2012, Textor 2014.…”
Section: Introductionunclassified
“…Anschließend wurde der Überstand (KM-ACS) in eine 12 ml Polypropylen Spritze aufgezogen. (Giraldo et al 2013, Hessel et al 2015, Ionita et al 2016. Dies bestätigt, dass es sich bei Orthobiologika nicht um standardisierte Therapeutika handelt, was die Etablierung von Behandlungsprotokollen erschwert und somit keine zuverlässige individuelle Aussage über die enthaltenen Inhaltsstoffe bzw.…”
Section: Introductionunclassified
See 1 more Smart Citation